1-Bromopropane-induced apoptosis in OVCAR-3 cells via oxidative stress and inactivation of Nrf2. (February 2021) - Yang, Guangtao; Xiang, Yingping; Zhou, Wei; Zhong, Xiaohuan; Zhang, Yanfang; Lin, Dafeng; Huang, Xianqing
The bromoalkane, 1-bromopropane (1-BP), may damage the reproductive system though oxidative stress, while the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) plays an important role in regulating intracellular antioxidant levels against oxidative stress. This study explored the role of oxidative stress and the Nrf2 signaling pathway in mediating the reproductive toxicity of 1-BP using the ovarian carcinoma cell line OVCAR-3 as an in vitro model of the human ovary. OVCAR-3 cells were treated with 1, 5, 10 and 15 mM 1-BP. After 24 h, the cellular reactive oxygen species and malondialdehyde concentrations significantly increased, while the superoxide dismutase activity decreased; translocation of Nrf2 from the cytosol to the nucleus as well as downstream protein expression of Nrf2-regulated genes heme oxygenase-1 and Bcl-2 was inhibited. Apoptosis was also observed, accompanied by increased caspase-3 and caspase-9 activity. The antioxidant vitamin C alleviated 1-BP-induced apoptosis by inhibiting caspase activity activating the Nrf2 signaling pathway. These findings suggested that 1-BP induced oxidative stress and apoptosis in OVCAR-3 cells through inactivation of Nrf2 signaling.